Disorganized resting‐state functional connectivity between the dorsal attention network and intrinsic networks in Parkinson's disease with freezing of gait. (13th September 2021) - Yu, Qian; Li, Qun; Fang, Weidong; Wang, Yuchan; Zhu, Yingcheng; Wang, Juan; Shen, Yalian; Han, Yu; Zou, Dezhi; Cheng, Oumei
Abstract: Freezing of gait (FOG) is a common and complex manifestation of Parkinson's disease (PD) and is associated with impairment of attention. The purpose of this study was to evaluate the functional network connectivity (FNc) changes between the dorsal attention network (DAN) and the other seven intrinsic networks relevant to attention, visual–spatial, executive and motor functions in PD with or without FOG. Forty‐three idiopathic PD patients (21 with FOG [FOG+] versus 22 without FOG [FOG−]) and 18 healthy controls (HC) were recruited in this study. The data‐driven independent component analysis (ICA) method was used to extract and analyze the above‐mentioned resting‐state networks (RSNs). Compared with FOG−, FOG+ displayed decreased positive connectivity between the DAN and medial visual network (mVN) and sensory‐motor network (SMN) and increased negative connectivity between the DAN and default mode network (DMN). The within‐network connectivity in the SMN and visual networks were decreased, whereas the connectivity within DMN was increased significantly in FOG+. Correlation analysis showed that the clock drawing test (CDT) scores were positively correlated with the functional connectivity of mVN ( r = 0.573, p = 0.008) and lateral visual network (lVN) ( r = 0.510, p = 0.022), the Timed Up and Go Test (TUG) duration were negatively correlated with the connectivity of SMN ( r = −0.629, p = 0.003), and the Frontal Assessment Battery (FAB) scores were negatively correlated with the connectivity of DMN in FOG+. Functional connectivity was changed in multiple intra‐networks in patients with FOG. Inordinate inter‐network connectivity between the DAN and other intrinsic networks may partly contribute to the mechanism of freezing. Abstract : In this study, we investigated functional network connectivity (FNc) changes between the dorsal attention network (DAN) and other resting‐state functional networks (RSNs) in PD patients with and without freezing of gait (FOG). We found decreased FNc between DAN and medial visual network (mVN) and sensory‐motor network (SMN), and an increased FNc between DAN and default mode network (DMN), suggesting that abnormal FNc between DAN and other RSNs may partly contribute to the mechanism of FOG.